COVID-19-Related Psychosocial Care in General Hospitals: Results of an Online Survey of Psychosomatic, Psychiatric, and Psychological Consultation and Liaison Services in Germany, Austria, and Switzerland - Schaefert, Rainer; Stein, Barbara; Meinlschmidt, Gunther; Roemmel, Noa; Huber, Christian G.; Hepp, Urs; Saillant, Stéphane; Fazekas, Christian; Vitinius, Frank (Frontiers in Psychiatry, 2022)
Background The coronavirus disease 2019 (COVID-19) pandemic was accompanied by new challenges for psychosocial health care to enable the support of affected patients, their families, and staff in general hospitals. In this study, we aimed to describe the structures and procedures put in place by psychosomatic, psychiatric, and psychological consultation and liaison (CL) services in German, Austrian, and Swiss general hospitals, and to elucidate the emerging needs for cooperation, networking, and improvement. Methods We conducted a cross-sectional online survey between December 2020 and May 2021, using a 25-item questionnaire derived from relevant literature, professional experience, and consultation with the participating professional societies. The survey was disseminated via national professional societies, relevant working and interest groups, and heads of the above-mentioned CL services. Results We included responses from 98 CL services in the analyses, with a total response rate of 55% of surveyed hospital CL services; 52 responses originated from Germany, 20 from Austria, and 26 from Switzerland. A total of 77 (79%) of the 98 responding CL services reported that “COVID-19-related psychosocial care” (COVID-psyCare) was provided in their hospital. Among these, 47 CL services (61%) indicated that specific cooperation structures for COVID-psyCare had been established within the hospital. A total of 26 CL services (34%) reported providing specific COVID-psyCare for patients, 19 (25%) for relatives, and 46 (60%) for staff, with 61, 12, and 27% of time resources invested for these target groups, respectively. Regarding emerging needs, 37 (48%) CL services expressed wishes for mutual exchange and support regarding COVID-psyCare, and 39 (51%) suggested future changes or improvements that they considered essential. Conclusion More than three-quarters of the participating CL services provided COVID-psyCare for patients, their relatives, or staff. The high prevalence of COVID-psyCare services targeting hospital staff emphasizes the liaison function of CL services and indicates the increased psychosocial strain on health care personnel during the COVID-19 pandemic. Future development of COVID-psyCare warrants intensified intra- and interinstitutional exchange and support. Trial Registration ClinicalTrials.gov NCT04753242, version 11 February 2021.